IMPLEMENTASI KEBIJAKAN RENCANA TATA RUANG WILAYAH DI KABUPATEN MAMUJU UTARA - Nasriaty, Nasriaty (Katalogis, 2016)
This study aimed to identify and analyze the implementation of the policy of spatial plans in North Mamuju regency. This type of research is qualitative. The informants are implementing policies Spatial Planning in the North Mamuju regency consisting of the Department of Housing and Spatial Planning Agency for the Development of Regional and PTSP and Investment, as well as the Agency One Stop Services and Investment. Collecting data using observations, interviews, and documentation, while menggunakanreduksi data analysis, data presentation, drawing conclusions / verification. Research results menunjukkanbahwaimplementasi policy Spatial Planning in the District of North Mamuju not running optimally, due to the content of policy (policy content) in terms of the resources still experiencing problems due to inadequate in terms of both quality and quantity, although in impelemtasinya already involve the target group, benefits to the community, provide the degree of change, demonstrating the accuracy of the decision-making implementation, and has introduced a procedure policy through socialization, while in terms of context implementation (environmental implementation) such as power, interests and strategies of the actors involved already indicated, the characteristic institutions and authorities have a strong commitment run policy, but the level of compliance and responsiveness of the public remains low as the community development process that is carried out individually or in groups do not yet have legal permits and land into a business most people are not destined for the policy.